Increased rounds of gonadotropin stimulation have side effects on mouse fallopian tubes and oocytes. Issue 3 (March 2018) - Di Nisio, Valentina; Rossi, Gianna; Palmerini, Maria Grazia; Macchiarelli, Guido; Tiboni, Gian Mario; Cecconi, Sandra
Abstract : In this study, it was evaluated if increased rounds of gonadotropin stimulation could affect in mice: (i) expression levels of proteins regulating cell cycle and DNA repair in fallopian tubes and (ii) meiotic spindle morphology of ovulated oocytes. To this end, adult female mice were subjected or not (Control) to 6 or 8 rounds of gonadotropin stimulation. Ovulated oocytes were incubated with anti A/B tubulin to evaluate spindle morphology. Fallopian tubes were analyzed to detect Cyclin D1, phospho-p53/p53, phospho-AKT/AKT, phospho-GSK3B/GSK3B, SOX2, OCT3/4, phospho-B-catenin/B-catenin, phospho-CHK1 and phospho-H2A.X protein levels. After 6 rounds, Cyclin D1, p53 and phospho-p53 contents were higher than Control. After 8 rounds, the contents of phosphorylated AKT, GSK3B and p53 as well as of total p53, Cyclin D1 and OCT3/4 significantly increased in comparison with Control. Conversely, SOX2 and B-catenin were similarly expressed among all experimental groups. The finding that phospho-CHK1 and phospho-H2A.X protein levels were undetectable supported the absence of extensive DNA damage. Oocytes number and percentage of normal meiotic spindles drastically decreased from 6 rounds onward. Altogether, our results demonstrated that 6 and 8 cycles of gonadotropin stimulation reduce mouse reproductive performances by inducing over-expression and over-activation of proteins controlling cell cycle progression in fallopian tubes and by impairing oocyte spindle.